Food security in transition countries: Conceptual issues and cross-country analyses - Peter Wehrheim; Doris Wiesmann (University of Bonn, Center for Development Research (ZEF), 2003)
Most methodological materials and analyses of food security pertain to the classical developing countries of the world. In this paper we discuss the question what pattern of food insecurity has developed across the transition countries? And, are there specific characteristics of food insecurity in the transition economies which can be attributed to the legacy of the socialist era? We argue that various legacies from the socialist system are decisive for today's economic and social environment in which food insecurity in these countries arises and has to be tackled. We discuss how the standard conceptual framework for the analysis of food security has to be adapted to take the specific characteristics of transition countries into account. Furthermore, we investigate if these legacies explain any significant differences in food security between transition and developing countries. We concluded from the analysis that on the macro-level similar basic factors determine food insecurity in transition countries and in developing countries. However, various legacies from the socialist era explain why transition countries have patterns, levels and trends of food insecurity distinct from developing countries. For instance, socialist legacies have contributed to the disproportionate decrease of the agricultural sector in most countries in transition in the 90s, and they still influence the pattern of food supply and consumption. Micro-studies would be needed to identify more precisely which affect the legacies have on food security at the household level.
Keywords: 330; Food Security and Poverty; Ernährungssicherung; Übergangswirtschaft; Institutionalismus; Osteuropa; Transformationsstaaten